Knowledge, awareness, and perception towards tuberculosis disease among International Islamic University Malaysia Kuantan students - Jamaludin, Thandar Soe Sumaiyah; Ismail, Nurhanis; Saidi, Sanisah (Elsevier Espa˜na, 2019)
Objective: This study aimed to survey the knowledge, awareness, and perception of International Islamic University Malaysia (IIUM), Kuantan campus students towards tuberculosis (TB) disease. Methods: A cross-sectional study was carried in six faculties (Kulliyyah) in IIUM Kuantan campus using an adopted self-administered questionnaire. Data were collected after obtaining ethical approval and analyzed the data by using SPSS version 20.0. Result: Relatively low level of knowledge and awareness (73.8%) and high stigma (67.9%) about TB disease was found among IIUM Kuantan students. There was a significant association between type of Kulliyyah and level of knowledge and awareness. The level of TB perception does not have any significant association with the level of knowledge and awareness of TB disease. Conclusion: These findings would suggest that more efforts should be made to improve the knowledge, awareness, and perception of students regarding TB disease.